TEKNOLOGI PERTANIAN BERBASIS EKOLOGI - Kevin Kevin; Budi Adelar Sukada (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Global Warming is one of the causes of ecological damage. It is caused by human activities that run at high intensity without considering their impact. Freight Transport, on the other hand, is a type of transportation activity that worsens such a condition due to its production of carbon dioxide and natural resources exploitation it exercises. However, Freight Transport activity occurs because a region requires supplies from other regions due to its disability  to meet its own needs. Agricultural Buildings are a solution to such problems by means of providing space that facilitates agricultural activities which could not be carried out because of poor land availability or land quality. This Agricultural Building is located in Pulokerto Village, Gandus District, Palembang City.  It is an agropolitan area that is threatened by urban development and creates damage to land resources. As such, it is a compound of buildings that operate the so-called. Organic Agriculture and Education program equipped with waste processing as well as self-sufficient input of energy from hydro-energy plant. This sub-program aims to ensure that existing agricultural activities do not exploit non-renewable resources and do not cause environmental damage. The compound ultimate is not only to repair and reduce ecological damage but also to become a new agricultural system and become a new agricultural platform where agriculture is one of the important sectors for the survival of life in a city.   Keywords:  Agriculture; Ecology;  Freight Transport; Global Warming.Abstrak Pemanasan Global menjadi salah satu penyebab kerusakan ekologi. Pemanasan Global disebabkan oleh aktivitas manusia yang berjalan dengan intensitas tinggi tanpa mempertimbangkan dampak dari aktivitas tersebut. Freight Transport atau yang lebih dikenal sebagai kegiatan logistik merupakan salah satu jenis aktivitas transportasi yang memperburuk keadaan ekologi akibat karbon dioksida dan eksploitasi sumber daya alam. Aktivitas Freight Transport ini sendiri terjadi karena tidak mampunya suatu daerah memenuhi kebutuhannya sendiri sehingga membutuhkan pasokan dari daerah lain. Bangunan dengan Teknologi Pertanian Berbasis Ekologi merupakan solusi dari permasalahan yang ada melalui penyediaan ruang pertanian baru yang memfasilitasi aktivitas pertanian yang sebelumnya tidak dapat dilakukan pada suatu area baik karena ketersediaan lahan maupun kualitas lahan yang tidak memenuhi kriteria ruang pertanian. Bangunan Pertanian ini berlokasi di Desa Pulokerto Kecamatan Gandus Kota Palembang dimana desa ini merupakan area agropolitan yang terancam oleh perkembangan kota dan kerusakan sumber daya tanah. Bangunan ini memiliki program yaitu Pertanian Organik dan Edukasi. Program-program ini difasilitasi oleh sub-program pengolahan limbah dan pengolahan energi secara mandiri melalui Hydroenergy Plant. Sub-program ini bertujuan agar aktivitas pertanian yang ada tidak mengeksploitasi sumber daya tidak terbarukan dan tidak menimbulkan kerusakan lingkungan. Bangunan Pertanian Berbasis Ekologi ini bertujuan memperbaiki dan mengurangi kerusakan ekologi serta menjadi wadah pertanian baru dimana pertanian merupakan salah satu sektor penting untuk kelangsungan kehidupan pada suatu kota.